Perfil das solicitações de apoio técnico no contexto de manutenção da rede brasileira de repositórios institucionais e de bibliotecas digitais locais de teses e dissertações - (:unkn) unknown (Instituto Brasileiro de Informação em Ciência e Tecnologia, 2017)
We present a qualitative and quantitative analysis of the profile of requests for technological support to institutions and users in Brazilian networks of open access scientific resources that are supported by IBICT. The information collected was based on a system of control of requests for assistance (Trello), which was adopted in September 2016. The results obtained point to the development of strategies and tools that lead to a greater efficiency in the use of time resources specialized support staff within the institutions.
Profile of technical support requests in the context of the maintenance of the Brazilian network of institutional repositories and local digital libraries of theses and dissertations
Keywords: Repositórios Digitais; Bibliotecas Digitais de Teses e Dissertações; Oasisbr; BDTD; Ciência da informação